2011
DOI: 10.1152/ajpendo.00387.2010
|View full text |Cite
|
Sign up to set email alerts
|

Variable penetrance of metabolic phenotypes and development of high-fat diet-induced adiposity in NEIL1-deficient mice

Abstract: Exposure to chronic and acute oxidative stress is correlated with many human diseases, including, but not limited to, cancer, heart disease, diabetes, and obesity. In addition to cellular lipids and proteins, cellular oxidative stress can result in damage to DNA bases, especially in mitochondrial DNA. We previously described the development of spontaneous late-onset obesity, hepatic steatosis, hyperinsulinemia, and hyperleptinemia in mice that are deficient in the DNA glycosylase nei-like 1 (NEIL1), which init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 54 publications
(68 reference statements)
4
68
0
Order By: Relevance
“…Animals. Construction and characterization of Neil1 knockout mice was previously described (31,32). The Neil1 genotype has been backcrossed >15 generations onto a C57Bl/6J background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals. Construction and characterization of Neil1 knockout mice was previously described (31,32). The Neil1 genotype has been backcrossed >15 generations onto a C57Bl/6J background.…”
Section: Methodsmentioning
confidence: 99%
“…Sterically, this adduct also represents the largest DNA base modification reported as a substrate for any DNA glycosylase. To extend the in vitro biochemical analyses to an in vivo repair assay, DNA adduct levels were measured in the livers of newborn WT and Neil1 −/− mice (31,32). We hypothesized that levels of AFB 1 -Fapy-dG would be significantly lower in WT vs. Neil1 −/− mice because the WT mice could repair these adducts via both the NER and BER pathways, whereas the Neil1 −/− mice would only repair this lesion via NER.…”
Section: Significancementioning
confidence: 99%
“…One of the most striking findings in multiple models of BER deficiency, primarily due to its unexpected nature, is that of an increased propensity to the development of obesity and metabolic syndrome in the absence of specific BER glycosylases [Vartanian et al, 2006;Sampath et al, 2011Sampath et al, , 2012b. While mice deficient in the BER glycosylases NEIL1 and OGG1 were initially developed to determine the role of BER in tumorigenesis, they were unexpectedly found to be prone to altered metabolic homeostasis.…”
Section: Actions Of Ber Glycosylases In Disease States Obesity and Mementioning
confidence: 99%
“…Subsequent studies in the NEIL1-deficient model indicated that these mice were prone to increased weight gain, fat accumulation, and glucose intolerance when exposed to a high-fat diet [Sampath et al, 2011]. This increased propensity to weight gain in Neil1 2/2 mice was a consequence of increased mtDNA damage, reduced mitochondrial content, and a reduction in whole body resting energy expenditure [Vartanian et al, 2006;Sampath et al, 2011]. Following the reports of obesity and metabolic disease in a NEIL1-deficient model, mice deficient for OGG1 were also reported to be prone to obesity and metabolic syndrome, relative to wild-type (WT) counterparts [Arai et al, 2006;Sampath et al, 2012b].…”
Section: Actions Of Ber Glycosylases In Disease States Obesity and Mementioning
confidence: 99%
“…Reduction or deficiency in DNA repair/replication enzyme activity is well documented to increase vulnerability for the development of cancer, neurodegenerative diseases, and aging (2). In addition, defective DNA repair enzymes are associated with the metabolic symptom; for example, DNA glycosylase (Neil1)-and OGG1-deficient mice are obese (3)(4)(5), and nucleotide excision repair protein ERCC1-XPF deficiency causes lipodystrophy (6). Furthermore, DNA damage response protein ataxia telangiectasia mutated (ATM) suppresses JNK activity through p53 signaling and mediates an antioxidant action that has been suggested to be relevant to the metabolic syndrome (7).…”
mentioning
confidence: 99%